ANALISIS ULASAN PENGGUNA APLIKASI TOKOPEDIA MENGGUNAKAN E-SERVQUAL - Reyniati Br Surbakti; Zulhalim Zulhalim; Akmal Budi Yulianto (Smart Education, 2026)
Abstract: This study aims to analyze the service quality of the Tokopedia application based on user reviews using the E-SERVQUAL approach. This study uses a qualitative method with a thematic content analysis approach. The research data comes from user reviews of the Tokopedia application available on the Google Play Store. The data were analyzed by grouping the reviews into seven E-SERVQUAL dimensions, namely efficiency, system availability, fulfillment, privacy, responsiveness, compensation, and contact. The validity of the data was tested through credibility, transferability, and dependability tests. The results show that user perceptions of Tokopedia's service quality vary. Some users consider Tokopedia's services to have provided easy access and fairly good data security. However, dominant complaints are still found in the dimensions of efficiency, system availability, fulfillment, and responsiveness, especially related to system stability, service speed, accuracy of order fulfillment, and customer service response. Based on these findings, Tokopedia needs to prioritize improving service quality in the dimensions that are most complained about by users. Keywords: E-SERVQUAL, electronic service quality, user reviews, Tokopedia. Abstrak: Penelitian ini bertujuan untuk menganalisis kualitas layanan aplikasi Tokopedia berdasarkan ulasan pengguna dengan menggunakan pendekatan E-SERVQUAL. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis isi tematik. Data penelitian bersumber dari ulasan pengguna aplikasi Tokopedia yang tersedia di Google Play Store. Data dianalisis dengan mengelompokkan ulasan ke dalam tujuh dimensi E-SERVQUAL, yaitu efficiency, system availability, fulfillment, privacy, responsiveness, compensation, dan contact. Keabsahan data diuji melalui uji credibility, transferability, dan dependability. Hasil penelitian menunjukkan bahwa persepsi pengguna terhadap kualitas layanan Tokopedia bersifat beragam. Beberapa pengguna menilai layanan Tokopedia telah memberikan kemudahan akses dan keamanan data yang cukup baik. Namun, masih ditemukan keluhan yang dominan pada dimensi efficiency, system availability, fulfillment, dan responsiveness, terutama terkait kestabilan sistem, kecepatan layanan, ketepatan pemenuhan pesanan, serta respons layanan pelanggan. Berdasarkan temuan tersebut, Tokopedia perlu memprioritaskan peningkatan kualitas layanan pada dimensi-dimensi yang paling banyak dikeluhkan pengguna. Kata kunci: E-SERVQUAL, kualitas layanan elektronik, ulasan pengguna, Tokopedia.